2018
DOI: 10.1002/stem.2938
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein M6B Interacts with TβRI to Activate TGF-β-Smad2/3 Signaling and Promote Smooth Muscle Cell Differentiation

Abstract: Smooth muscle cells (SMCs), which form the walls of blood vessels, play an important role in vascular development and the pathogenic process of vascular remodeling. However, the molecular mechanisms governing SMC differentiation remain poorly understood. Glycoprotein M6B (GPM6B) is a four‐transmembrane protein that belongs to the proteolipid protein family and is widely expressed in neurons, oligodendrocytes, and astrocytes. Previous studies have revealed that GPM6B plays a role in neuronal differentiation, my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…In our experiments, serotonin could promote the proliferation of PCa cell lines, which is consistent with a previous study [ 14 , 15 , 19 ]. On the other side, the overexpression of GPM6B can reverse the effect of serotonin in PCa cell growth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our experiments, serotonin could promote the proliferation of PCa cell lines, which is consistent with a previous study [ 14 , 15 , 19 ]. On the other side, the overexpression of GPM6B can reverse the effect of serotonin in PCa cell growth.…”
Section: Discussionsupporting
confidence: 93%
“…Relevant studies have shown that GPM6B can bind to SERT and result in a significant reduction in serotonin uptake [ 14 ]. GPM6B also plays a regulatory role in smooth muscle cell differentiation [ 15 ]. Oncological research on GPM6B has gradually attracted attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, GlialCAM and MLC1 have been shown to influence intracellular signaling pathways controlling astrocyte activation and proliferation. Several proteins have been identified related to cell signaling within this proteome, such as three different GPCRs (GPR37, GPR37L1 and GPRC5B), a tetraspanin (CD9) ( 41 ) and the four transmembrane domain proteins Glycoprotein M6A and M6B ( 42 , 43 ). Considering the role played by GPCRs, we hypothesize that some of the signaling pathways involving MLC proteins might be caused by the activity of these GPCRs.…”
Section: Discussionmentioning
confidence: 99%
“…GDF10 plays an important role in cell proliferation and differentiation and is also known as BMP-3B due to its close relationship with bone morphogenetic protein-3 (BMP3), another member of the TGF-β superfamily [12]. TGF-β signals through three cell surface receptors, namely TGFBR1/2/3 [13,14]. Stimulation of TGFBR2 activates TGFBR1, which phosphorylates Smad2/3.…”
Section: Introductionmentioning
confidence: 99%